2-D Localization, Angular Separation and Vital Signs Monitoring Using a SISO FMCW Radar for Smart Long-Term Health Monitoring Environments - Mercuri, Marco; Sacco, Giulia; Hornung, Rainer; Zhang, Peng; Visser, Hubregt J.; Hijdra, Martijn; Liu, Yao-Hong; Pisa, Stefano; van Liempd, Barend; Torfs, Tom (IEEE internet of things journal, 2021)
A single-input and single-output (SISO) frequency-modulated continuous wave (FMCW) radar architecture is proposed and in vivo demonstrated for remote 2-D localization (range and angular information) and vital signs monitoring of multiple subjects. The radar sensor integrates two frequency scanning antennas which allow angular separation and enable determining a 2-D map (range versus angle) of a room environment from which people can be distinguished from objects and clutter. After technical tests to validate the functionality of the proposed architecture and data processing algorithm, a practical setup was successfully demonstrated to locate human volunteers, at different absolute distances and orientations, and to retrieve their respiratory and heart rate information. Experimental results show that this radar sensor can monitor accurately the vital signs of multiple subjects within typical room settings, reporting maximum mean absolute errors of 0.747 breaths-per-minute and 2.645 beats-per-minute, respectively, for respiration rate and heartbeat. Practical applications arise for Internet of Things (IoT), ambient-assisted living, healthcare, geriatric and quarantine medicine, automotive, rescue and security purposes.